Bagaimana Hubungan Pusat dan Daerah Pasca Penetapan Undang-Undang Cipta Kerja? Kasus Penetapan Pajak Daerah - Shandy, Nabila Alif Radika; Wardhana, Allan Fatchan Ghani (Universitas Islam Negeri Raden Intan Lampung, 2022)
The relationship between the Central Government and Regional Governments in determining regional tax rates and regional levies has overlapping authorities after the enactment of the Job Creation Act. This study proposes two problem formulations. First, how is the relationship between the central government and regional governments in determining local tax rates after the enactment of Law Number 11 of 2020 concerning Job Creation? Second, what are the juridical implications of setting local tax rates after the enactment of Law Number 11 of 2020 on the Authority of Regional Governments? The research method used is juridical-normative by using primary, secondary, and tertiary legal materials. The approach used is a statutory and conceptual approach. The results reveal that first, the relationship between the Central Government and Regional Governments in determining regional tax rates and regional retributions after the enactment of the Job Creation Law is carried out by the Regional Government with the involvement of the Central Government. It is known that at the time of the formation of regulations in the field of regional tax rates, the Central Government can change the tax rates and levy rates by determining the nationally applicable tax and levy rates and evaluating both Regional Regulations and Draft Regional Regulations regarding taxes and levies that hinder investment ecosystems and ease of doing business. Second, prior to the enactment of the Job Creation Act, the regional government had the authority to determine regional tax rates and regional retributions, so that in this case, the decentralization system runs fully, while after the enactment of the Job Creation Act, the regional government's authority in administering the government, in particular the area of regional taxes and levies, does not fully reflect the decentralized system due to intervention from the central government.Keywords: Relations, Central Government, Local Government, Tariffs, Local Taxes